The Giver - Lowry, Lois (Boston : Houghton Mifflin Harcourt, 2014)
Given his lifetime assignment at the Ceremony of Twelve, Jonas becomes the receiver of memories shared by only one other in his community and discovers the terrible truth about the society in which he lives.
Keywords: Individuality -- Juvenile fiction; Liberty -- Juvenile fiction; Social control -- Juvenile fiction; Social prediction -- Juvenile fiction; Memory -- Juvenile fiction; Dystopias -- Juvenile fiction; Individuality -- Fiction; Freedom -- Fiction; Social control -- Fiction; Social prediction -- Fiction; Memory -- Fiction; Dystopias -- Fiction; Dystopias; Individuality; Liberty; Memory; Social control; Social prediction; Science fiction; Fiction; Young adult works